Vulnerability of Protoxylem and Metaxylem Vessels to Embolisms and Radial Refilling in a Vascular Bundle of Maize Leaves - Hwang, Bae Geun; Ryu, Jeongeun; Lee, Sang Joon (Frontiers in Plant Science, 2016)
Regulation of water flow in an interconnected xylem vessel network enables plants to survive despite challenging environment changes that can cause xylem embolism. In this study, vulnerability to embolisms of xylem vessels and their water-refilling patterns in vascular bundles of maize leaves were experimentally investigated by employing synchrotron X-ray micro-imaging technique. A vascular bundle in maize consisted of a protoxylem vessel with helical thickenings between two metaxylem vessels with single perforation plates and nonuniformly distributed pits. When embolism was artificially induced in excised maize leaves by exposing them to air, protoxylem vessels became less vulnerable to dehydration compared to metaxylem vessels. After supplying water into the embolized vascular bundles, when water-refilling process stopped at the perforation plates in metaxylem vessels, discontinuous radial water influx occurred surprisingly in the adjacent protoxylem vessels. Alternating water refilling pattern in protoxylem and metaxylem vessels exhibited probable correlation between the incidence location and time of water refilling and the structural properties of xylem vessels. These results imply that the maintenance of water transport and modulation of water refilling are affected by hydrodynamic roles of perforation plates and radial connectivity in a xylem vascular bundle network.